Sosialisasi Pengenalan Dunia Kampus Kepada Siswa SMA Terpadu Darur Roja - Mella Nanda Nurohmah (Universitas Madani Indonesia, 2025)
Community service is implemented through socialization with Darur Roja Integrated High School students in order to fulfill the tri-dharma of higher education, which recognizes that community service can actively address issues that arise in the community, one of which is students' ignorance of the campus. There is intense competition among students throughout Indonesia to gain admission to their preferred institutions and majors because high school graduates must want a solid profession in line with their goals. Counseling or socializing strategies, campus-related movies, motivational videos, and presentation tactics of introductory content are used to address issues pertaining to students' ignorance of higher education. Discussion sessions are then used to continue the conversation. It is hoped that grade 12 students at Darur Roja Integrated High School will learn about education via this socialization.